A Causal Model of Physical Appearance Perfectionism and Women’s Body Image Concern: The Mediating Role of Appearance-Based Comparisons on Instagram - Alidosti, Fatemeh; Soghraei Khader, Zahra; Bakhtiari, Mahdieh (Psychology of Woman Journal, 2022)
The present study investigated the relationship between physical appearance perfectionism and body image concern with the mediation of appearance-based comparisons on Instagram. This study was a type of primary research done by correlation method. In this research, the statistical population was women aged 18 and over who used Instagram, and the sample size included 324 people who were selected in an accessible manner. The questionnaires used in this research were: The physical Appearance Perfectionism Questionnaire by Young and Stoeber (2012) and Body Image Concern Questionnaire by Littleton et al. In order to analyze the research data, the results obtained from the Pearson correlation coefficients showed a positive and significant relationship between the research variables. Also, the path analysis method results showed that after correcting and removing the non-significant path of the hope-to-perfection component to body image concern in the initial model, the final model was confirmed with a perfect fit (χ2/df=3.23, RSMEA=0.08, GFI=1, AGFI=0.95, CFI=1). Overall, it can be concluded that appearance-based comparisons on Instagram have significantly mediated the relationship between physical appearance perfectionism and body image concern.